Structural and functional characteristics of soil microbial community in a Pinus massoniana forest at different elevations - Zhang,Jian; Xu,Ming; Zou,Xiao; Chen,Jin (PeerJ, 2022)
Shifts in forest soil microbial communities over altitudinal gradients have long been attracting scientific interest. The distribution patterns of different soil microbial communities along altitudinal gradients in subtropical mountain forest ecosystems remain unclear. To better understand the changes in soil microbial communities along an altitude gradient, we used Illumina MiSeq metagenome sequencing technology to survey the soil microbial communities in a Pinus massoniana forest at four elevations (Mp1000, Mp1200, Mp1400, Mp1600) and in a tea garden in Guizhou Leigong Mountain in Southwestern China. We observed that the richness of bacteria, fungi, and viruses in the soil microbial community changed in a unimodal pattern with increasing elevation while that of Archaea first increased significantly, then decreased, and finally increased again. Euryarchaeota and Thaumarchaeota were the predominant Archaea, Proteobacteria and Acidobacteria were the predominant bacterial groups, Ascomycota and Basidiomycota were the predominant fungal groups, and Myoviridae, Podoviridae, and Siphoviridae were the predominant virus groups. Amino acid transport and metabolism, energy production and conversion, signal transduction mechanisms, and DNA replication, restructuring and repair were the predominant categories as per NOG function gene-annotation. Carbohydrate metabolism, global and overview map, amino acid metabolism, and energy metabolism were predominant categories in the KEGG pathways. Glycosyl transferase and glycoside hydrolase were predominant categories among carbohydrate enzyme-functional genes. Cluster, redundancy, and co-occurring network analyses showed obvious differences in the composition, structure, and function of different soil microbial communities along the altitudinal gradient studied. Our findings indicate that the different soil microbial communities along the altitudinal gradient have different distribution patterns, which may provide a better understanding of the mechanisms that determine microbial life in a mid-subtropical mountain forest ecosystem.
Keywords: Altitudinal gradient; Metagenome; Pinus massoniana; Community structure and function; Subtropical mountain forest; Soil microbial communities